Inside Front Cover: Cover Image, Volume 22, Issue 1. Issue 1 (13th December 2018) - Bergelson, Elika; Casillas, Marisa; Soderstrom, Melanie; Seidl, Amanda; Warlaumont, Anne S.; Amatuni, Andrei
Abstract : The cover image is based on the Paper What Do North American Babies Hear? A large‐scale cross‐corpus analysis, by Elika Bergelson et al., DOI10.1111/desc.12724